Analisis Modal Sosial Terhadap Kinerja dan Produktivitas Bisnis Perempuan: Kajian UMKM di Kota Padang - Elsa Widia; Sri Mona Octafia (Research Institute and Community Engagement of UIN MADURA, 2023)
Micro, Small, and Medium Enterprises (MSMEs) led by women have been able to contribute to the national economy, with more than half of MSMEs in Indonesia being operated by women. However, this contribution is still not maximized, as predominantly, women-led MSMEs in Indonesia operate on a small scale and have informal status. The dual role, at times, becomes a reason for them to choose a small scale, especially for women who also work as homemakers. Generally, research tends to focus on the overall performance of MSMEs without specific studies on social capital. There is very little research addressing women-led MSMEs and their actions. This study aims to explore the entrepreneurial concept implemented by women-led MSMEs, considering not only managerial capabilities but also social capital elements such as trust levels, mutual assistance, participation, and moral/cultural traditions. This research will analyze the role of social capital resources in women-led MSMEs in Padang City, specifically in the Koto Tangah sub-district, using qualitative analysis methods such as Descriptive Crosstabs Analysis and Binary Logistic Regression Analysis. Data will be obtained through questionnaires, interviews, and observations. The research results reveal that social capital is deemed capable of building a strong network and has the potential to enhance the performance of women-led MSMEs in Padang City. (UMKM Perempuan telah mampu berkontribusi pada perekonomian nasional bahkan diketahui lebih dari setengah UMKM di Indonesia dijalankan oleh perempuan. Namun kontribusi tersebut masih belum maksimal, karena secara dominan UMKM perempuan di Indonesia berada pada skala yang kecil dan status informal. Peran ganda kadang kala juga menjadi suatu alasan mereka memilih di skala yang kecil, khususnya bagi UMKM perempuan yang juga berprofesi sebagai ibu rumah tangga. Pada umumnya penelitian hanya memfokuskan kinerja UMKM secara umum tanpa adanya kajian yang spesifik tentang modal sosial. Sangat sedikit penelitian yang membahas mengenai UMKM perempuan dan cara mereka bertindak. Penelitian ini akan membahas konsep kewirausahaan yang dilakukan oleh UMKM perempuan dengan memadukan tidak hanya masalah kemampuan managerial tapi juga terkait modal sosial seperti tingkat kepercayaan, tolong menolong, pastisipasi dan moral/adat istiadat. Penelitian ini akan menganalisis mengenai peran sumber daya modal sosial pada UMKM Perempuan di Kota Padang khususnya di Kecamatan Koto Tangah menggunakan analisis kualitatif seperti Analisis Deskriptif Crosstabs dan Analisis Regresi Binary Logistik. Data diperoleh melalui metode kuisioner, wawancara dan Observasi. Hasil penelitian mengungkapkan bahwa modal sosial dinilai dapat membangun sebuah jaringan yang kuat dan berpotensi dalam peningkatan kinerja UMKM Perempuan di Kota Padang.)